Identification, localization, and distribution of the PilT protein in Neisseria gonorrhoeae. - Brossay, L (1994)
A monoclonal antibody (MAb) directed against a highly conserved protein of Neisseria gonorrhoeae with a molecular size of 40 kDa was isolated and characterized. The protein antigen detected by this MAb was detected by enzyme-linked immunosorbent assay and immunoblotting in all strains of N. gonorrhoeae tested across a wide range of serovars. The 40-kDa protein was found to be expressed at relatively low levels and localized to both the cytosolic and cytoplasmic membrane fractions. Screening of a lambda gt11 expression library derived from gonococcal genomic DNA with the anti-40-kDa MAb and DNA sequence analysis suggested that the 40-kDa protein and the product of the gonococcal pilT gene were identical. Immunoblotting analysis of gonococcal mutants carrying defined mutations in the pilT gene confirmed that the 40-kDa protein was indeed PilT. The N-terminal sequence derived by microsequencing of the protein purified from gonococci led to the correction of the previously published pilT gene sequence. Sequencing of the pilT gene from three different strains revealed an extremely high degree of conservation at both the amino acid and DNA levels.